Theoretical Investigations of the [Ni(3-allyl)(PMe3)]+ Catalyzed Ethen Dimerization and the Mechanism of Active Species Formations - الباني, نبيل (Latakia University Journal -Basic Sciences Series, 2021)
The mechanism of formation of the active compounds of the [Ni(h3-allyl)(PMe3)]+ complex was investigated using the B3LYP method with basis sets 6-31+G(d), 6-311+G (d, p), and def2-SVP for all atoms except for the nickel atom (for it, two basis sets LANL2DZ and def2-TZVP were used). The theoretical results show that the formation of the metallic hydride compounds (LnNi - H) requires very high Gibbs free energy, while the formation of the alkyl metal species (LnNi-CH2CH3) is more thermodynamically stable. The metallic hydride compounds can represent an active compounds, but the alkyl metal component acts as the active catalyst. The theoretical results indicate that all the intermediates and transitions states formed along the catalytic cycle of ethen dimerization by the active alkyl catalyst are thermodynamically stable. When using the B3LYP/def2-SVP level of theory with the def2-TZVP basis set for Ni, it was observed that it exhibited lower changes in the free Gibbs energies along the catalytic cycle than other levels of theory.